2014
DOI: 10.1002/berj.3144
|View full text |Cite
|
Sign up to set email alerts
|

Worlds apart? The nature and quality of the educational experiences of pupils with a statement for special educational needs in mainstream primary schools

Abstract: from the Deployment and Impact of Support Staff (DISS) project showed that support from teaching assistants (TAs) had a strong negative impact on the academic progress of pupils, and this applied particularly to pupils with a statement of special educational needs (SEN). Although the DISS project found that such pupils experienced less contact with teachers, little is known about school-and classroom-level decision-making relating to provision. This paper addresses the nature and quality of the educational exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 22 publications
(29 reference statements)
3
35
0
2
Order By: Relevance
“…Conversely, Waddington and Reed's () comparison of the effects of mainstream and special school on National Curriculum outcomes in learners with ASD in four local authorities in England concluded that mainstream learners have no greater academic success than learners in special schools. Similar to Webster and Blatchford (), they reported that access to TAs correlated negatively with academic outcomes for those children in mainstream provision. De Boer et al's () Norwegian study also referred to a negative impact of TAs: reducing the possibility of contact between the student with special educational needs and his/her peers and thus reducing the potential for inclusion.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Conversely, Waddington and Reed's () comparison of the effects of mainstream and special school on National Curriculum outcomes in learners with ASD in four local authorities in England concluded that mainstream learners have no greater academic success than learners in special schools. Similar to Webster and Blatchford (), they reported that access to TAs correlated negatively with academic outcomes for those children in mainstream provision. De Boer et al's () Norwegian study also referred to a negative impact of TAs: reducing the possibility of contact between the student with special educational needs and his/her peers and thus reducing the potential for inclusion.…”
Section: Discussionsupporting
confidence: 69%
“…Staff expertise is indeed crucial to the success of inclusion. Webster and Blatchford () extended the literature on deficiencies in teachers’ and TAs’ special educational needs expertise in mainstream schools. The Making a Statement study tracked 48 Year 5 pupils with Statements for either moderate learning difficulties or BESD, because these categories were likely to detect school support factors connected to problems with learning and classroom engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Both reports suggest the use of continued professional development (CPD) following ITT for teachers to gain a better knowledge of the subject. However, Webster and Blatchford's (2015) results suggest that this may not be happening. Consequentially, it is important to know whether teachers believed their ITT covered dyslexia sufficiently and whether they have received any CPD training in addition to their ITT.…”
Section: Introductionmentioning
confidence: 96%
“…However, quantitative and qualitative analyses of these data identified several key concerns. For more on the MAST study, see Webster and Blatchford (, , in press).…”
mentioning
confidence: 99%